PENDAMPINGAN PENYUSUNAN MODEL BISNIS CANVAS PADA UNIT BISNIS PAKAN TERNAK BUMDES DHARMA PITALOKA DESA CURAH COTTOK SITUBONDO - Rachmawati, Dyna; Joewono, Andrew; Anggorowati, Adriana Anteng (Universitas Mataram, 2024)
BUMDes Dharma Pitaloka is a business entity owned by Curah Cottok village, Kapongan District, Situbondo Regency. Since the Covid-19 pandemic, BUMDes income has decreased from both transportation and educational tourism businesses called Cottok Innovations Park (CIP). This encouraged the management of BUMDes Dharma Pitaloka to diversify its business by establishing a new business unit, namely animal feed. This animal feed has as its main raw material shrimp heads which are waste from a shrimp export company located near the village of Curah Cottok. The aim of this activity to prepare for the establishment of this animal feed business unit at BUMDes Dharma Pitaloka. Preparing a business plan is one aspect that must be prepared by the animal feed business unit. The implementation method is mentoring carried out in 2 ways, namely: tutorials and independent activities. The tutorial was carried out using a zoom meeting and video tutorial on filling out the business model canvas. The independent activity is the preparation of a business plan using a canvas model by 2 BUMDes administrators. This mentoring activity produces an output, namely a business plan for the animal feed business unit. This canvas model business plan is apparently easy to understand for BUMDes administrators who will be in charge of the animal feed business unit. This concludes that this mentoring activity is quite effective because it can produce output. This canvas model business plan will be used by the management of BUMDes Dharma Pitaloka in carrying out operational activities of the poultry feed business unit.